A revision of Cissidium Motschulsky (Coleoptera: Ptiliidae) with seventy seven new species - Darby, Michael (European Journal of Taxonomy, 2020)
This paper examines the described species of Cissidium and adds 77 new ones based on a study of material in the Manchester Museum, UK, the Natural History Museum, London, UK and in the possession of Dr Yoshihiro Sawada, Japan. The new taxa are: Cissidium advena sp. nov., C. amazonicum sp. nov., C. amieuense sp. nov., C. angulatum sp. nov., C. angusi sp. nov., C. apterum sp. nov., C. arcuatum sp. nov., C. aristophanousi sp. nov., C. besucheti sp. nov., C. bifoveolatum sp. nov., C. bilineatum sp. nov., C. bomjesus sp. nov., C. brachypterum sp. nov., C. ceylonicum sp. nov., C. clareae sp. nov., C. cryptophagoides sp. nov., C. davaoense sp. nov., C. deanei sp. nov., C. delicatum sp. nov., C. dewhurst sp. nov., C. dividuum sp. nov., C. dybasi sp. nov., C. eciton sp. nov., C. ecuadoriense sp. nov., C. faustum sp. nov., C. flavum sp. nov., C. franzi sp. nov., C. fraternum sp. nov., C. glabratum sp. nov., C. greensladei sp. nov., C. houailou sp. nov., C. ibicarense sp. nov., C. impressum sp. nov., C. inexspectatum sp. nov., C. insulare sp. nov., C. kolombangaricum sp. nov., C. lamington sp. nov., C. lawrencei sp. nov., C. loebli sp. nov., C. logunovi sp. nov., C. losbanos sp. nov., C. lucidulum sp. nov., C. luctuosum sp. nov., C. mahleri sp. nov., C. mindanao sp. nov., C. misellum sp. nov., C. modestum sp. nov., C. montanum sp. nov., C. murphyi sp. nov., C. mussardi sp. nov., C. noumeae sp. nov., C. obscenum sp. nov., C. obscurum sp. nov., C. obsoletum sp. nov., C. opacum sp. nov., C. orami sp. nov., C. peruviense sp. nov., C. pilosellum sp. nov., C. pinense sp. nov., C. plaumanni sp. nov., C. puncticolle sp. nov., C. riparium sp. nov., C. robustum sp. nov., C. rogeri sp. nov., C. seditiosum sp. nov., C. semicalvum sp. nov., C. similatum sp. nov., C. steeli sp. nov., C. subangulatum sp. nov., C. subfaustum sp. nov., C. sueae sp. nov., C. trangse sp. nov., C. upiense sp. nov., C. visendum sp. nov., C. waginicum sp. nov., C. werneri sp. nov. and C. yoruba sp. nov. The division of the genus is discussed and five species groups are established. The majority of the new species are the first records of Cissidium for the 28 countries represented.